1995
DOI: 10.1006/viro.1995.1228
|View full text |Cite
|
Sign up to set email alerts
|

The DNA Sequence of Human Herpesvirus-6: Structure, Coding Content, and Genome Evolution

Abstract: The complete DNA sequence was determined for strain U1102 of human herpesvirus-6, a CD4+ T-lymphotropic virus with disease associations in immunodeficient settings and a possible complicating factor in AIDS. The genome is 159,321 bp in size, has a base composition of 43% G + C, and contains 119 open reading frames. The overall structure is 143 kb bounded by 8 kb of direct repeats, DRL (left) and DRR (right), containing 0.35 kb of terminal and junctional arrays of human telomere-like simple repeats. Since eight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

13
532
1
10

Year Published

1997
1997
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 535 publications
(556 citation statements)
references
References 0 publications
13
532
1
10
Order By: Relevance
“…Five microliters of DNA extract from whole blood, serum, or CSF was subjected to quantitative HHV-6 PCR, and the result was compared with the result of quantitative PCR for human ␤-globin (25). The HHV-6 PCR (8) amplifies DNA from part of the HHV-6 U67 gene, of which there is only one copy per virus genome (16). Since there are 2 copies of ␤-globin/cell, the number of viral DNA copies/cell is 2 ϫ HHV-6 DNA copies/␤-globin DNA copies (46).…”
Section: Patients (I) Group 1 Routine Diagnosis Patientsmentioning
confidence: 99%
“…Five microliters of DNA extract from whole blood, serum, or CSF was subjected to quantitative HHV-6 PCR, and the result was compared with the result of quantitative PCR for human ␤-globin (25). The HHV-6 PCR (8) amplifies DNA from part of the HHV-6 U67 gene, of which there is only one copy per virus genome (16). Since there are 2 copies of ␤-globin/cell, the number of viral DNA copies/cell is 2 ϫ HHV-6 DNA copies/␤-globin DNA copies (46).…”
Section: Patients (I) Group 1 Routine Diagnosis Patientsmentioning
confidence: 99%
“…The HHV-6A/B genome consists of a unique sequence (U) that is flanked by G-rich direct repeat regions (DR) that harbor the packaging sequences (pac1 and pac2) and two arrays of either perfect or imperfect telomeric repeats (TMR) at the genome termini (22)(23)(24)(25)(26). The presence of these repeats at the ends of the viral genomes and the fact that chromosomal integration occurs in telomeres led to the hypothesis that HHV-6A/B integrates the human genome by homologous recombination (HR) between viral TMRs and chromosomal telomeric sequences (10,27).…”
mentioning
confidence: 99%
“…Additionally, some are encoded by virus genes. To date, 20 putative viral GCR genes have been discovered: 2 in poxvirus genomes (21,44), 11 in betaherpesvirus genomes (9,22,33,49,54), and 7 in gammaherpesvirus genomes (4,26,48,57,63). The majority of these genes was found to be similar to genes encoding cellular chemokine receptors.…”
mentioning
confidence: 99%
“…The KSHV chemokine receptor was also shown to stimulate cellular proliferation (4), transformation, and angiogenesis (7). A distinctive set of chemokine-like receptors is exclusively encoded by betaherpesviruses: HCMV UL33 (23), rat cytomegalovirus (RCMV) R33 (9), murine cytomegalovirus (MCMV) M33 (54), and human herpesvirus 6 and 7 (HHV-6 and -7) U12 (33,49). Recently, we found that the RCMV R33 gene is essential for the pathogenesis of viral infection in vivo and that unlike wild-type (wt) virus, an RCMV R33 null mutant could neither enter nor replicate in salivary gland epithelial cells of infected rats (9).…”
mentioning
confidence: 99%
See 1 more Smart Citation